Community-led change: Progress toward policy, systems, and environmental impacts through the Catalyzing Communities initiative - Travis R. Moore; Yuilyn A. Chang Chusan; Emily Sanderson; Larissa Calancie; Erin Hennessy; Julia M. Appel; Mary Ulseth; Christina D. Economos (PLoS ONE, 2025)
Purpose and objectives This study evaluated progress toward policy, systems, and environmental (PSE) changes through community-led actions supported by the Catalyzing Communities initiative, guided by Stakeholder-Driven Community Diffusion (SDCD) theory. Objectives included assessing community action implementation, evaluating SDCD-informed strategies’ role in enhancing capacity, and identifying contextual factors influencing progress towards PSE changes. Intervention approach Catalyzing Communities engaged 23 key partners across eight U.S. communities. These partners led committees of 110 local champions and integrated local insights and resources into community-led actions. Capacity-building strategies supported action prioritization and implementation. Evaluation methods A mixed-methods approach included web surveys and follow-up interviews. Surveys assessed action implementation, while interviews explored impacts and contextual factors. Data were analyzed using thematic analysis, supported by an iteratively developed codebook and double coding. Results Fourteen changemakers completed surveys and ten participated in interviews. They led 82 local champions across six communities in prioritizing and implementing 21 community-informed actions. Actions differed across communities based on local priorities, including enhancing early childhood and school programs, improving food access, promoting active living, and fostering community connections. Most actions were ongoing, in progress at the time of data collection, and partially successful in reaching target populations. Capacity-building strategies – such as peer networking, tools like causal loop diagrams, and technical assistance – were critical for building relationships, enhancing systems thinking, and securing funding. Contextual factors, including committee synergy, readiness, organizational capacity, and the impact of COVID-19, shaped progress toward PSE changes.